MARRIAGE: A Randomized Trial of Moxonidine Ramipril or in Combination With Ramipril in Overweight Patients With Hypertension and Impaired Fasting Glucose or Diabetes Mellitus. Impact on Blood Pressure, Heart Rate and Metabolic Parameters - Paul Valensi MD; Selim Jambart MD (SAGE Publishing, 2024)
Background Moxonidine, an imidazoline I 1 receptor agonist, is an effective antihypertensive drug that was shown to improve insulin sensitivity. RAAS-blockers are recommended as first-line therapy in patients with diabetes, alone or in combination with a calcium-channel antagonist or a diuretic. Aims This study compared the effects of moxonidine and ramipril on blood pressure (BP) and glucose metabolism in overweight patients with mild-to-moderate hypertension and impaired fasting glucose or type 2 diabetes. Methods Treatment-naïve patients for hypertension and dysglycemia were randomized to 12 weeks of double-blind moxonidine 0.4 mg or ramipril 5 mg once-daily treatment. At 12 weeks, for a further 12 weeks non-responders received combination of mox/ram, while responders continued blinded treatment. Results Moxonidine and ramipril were equivalent in lowering SiDBP and SiSBP at the end of the first 12 weeks. The responder rate was approximately 50% in both groups, with a mean SiDBP and SiSBP decrease of 10 and 15 mm Hg in the responders, respectively. The normalization rate (SiDBP < 85 mm Hg) was non significantly different between treatments groups. Moxonidine reduced heart rate (HR) (average −3.5 bpm, p  = 0.017) during monotherapy, and when added to ramipril. HbA1c decreased significantly at Week 12 in both groups. Neither drug affected glucose or insulin response to the oral glucose tolerance test. In non-responders, moxonidine/ramipril combination further reduced BP without compromising metabolic parameters. Conclusion Moxonidine 0.4 mg and ramipril 5 mg were equally effective on BP lowering and were well tolerated and mostly metabolically neutral either as monotherapies or in combination. HR was lowered on moxonidine treatment.